ANALISA KUALITAS DAYA TRANSFORMATOR 1 MVA DAN 200 KVA DI UPT BALAI YASA SURABAYA GUBENG - Rani Iswahyu Ramadini; Budiono, Gatut; Wardah, Izzah Aula (Universitas Islam Lamongan, 2023)
UPT Balai Yasa Surabaya Gubeng has electrical equipment with non-liner load characteristics, which may affect power rating in accordance with PLN and IEEE 519 – 2014 standards. Non-linear loads result in non-compliant power quality parameter values ​​such as voltage, power factor, frequency, and harmonics. The efficiency of the transformer is also determined. due to the generated power from the transformer to the load. This study was conducted by collecting and processing data from LVMDP. It was found that several parameters did not comply with PLN standards. The power factor of LVMDP 1 MVA and LVMDP 200 KVA are 0.8 and 0.7 respectively. Meanwhile, all voltage and frequency ​​of 1 MVA and 200 KVA LVMDP are still according to PLN standards. Whereas, the harmonics of LVMDP 1 MVA THDi R phase (26.18%), S phase (18.83%), THDv T phase (8.86%), and LVMDP 200 KVA THDv T phase (5.58%) are not in accordance with IEEE 519 – 2014 standards. Thus, single tuned filter were simulated which reduce the harmonics of the systems and increase the efficiency of the transformator.